SufR, a [4Fe-4S] Cluster-Containing Transcription Factor, Represses the sufRBDCSU Operon in Streptomyces avermitilis Iron-Sulfur Cluster Assembly - Cheng, Yaqing (Appl Environ Microbiol, 2020)
Iron-sulfur (Fe-S) clusters are ubiquitous and versatile inorganic cofactors that are crucial for many fundamental bioprocesses in nearly all organisms. How cells maintain Fe-S cluster homeostasis is not well understood in Gram-positive bacteria. Genomic analysis showed that the Suf system, which is encoded by the sufRBDCSU operon, is the sole Fe-S cluster assembly system in the genus Streptomyces. Streptomyces avermitilis is the industrial producer of avermectins, which are widely used as agricultural pesticides and antiparasitic agents. sufR (SAV6324) encodes a putative ArsR-family transcriptional regulator, which was characterized as a repressor of the sufRBDCSU operon in this investigation. Spectroscopy and mass spectrometry demonstrated that anaerobically isolated SufR contained an oxidation-sensitive [4Fe-4S] cluster and existed as a homodimer. Electrophoretic mobility shift assays (EMSAs) and DNase I footprinting analyses revealed that [4Fe-4S]-SufR bound specifically and tightly to a 14-bp palindromic sequence (CAAC-N6-GTTG) in the promoter region of the sufR operon, repressing expression of the sufRBDCSU operon. The presence of the [4Fe-4S] cluster is critical for the DNA-binding activity of SufR. Cys(182), Cys(195), and Cys(223) in the C-terminal region of SufR are essential for [4Fe-4S] cluster coordination, but Cys(178) is not. The fourth non-Cys ligand in coordination of the [4Fe-4S] cluster for SufR remains to be identified. The findings clarify the transcriptional control of the suf operon by [4Fe-4S] SufR to satisfy the various Fe-S cluster demands. SufR senses the intracellular Fe-S cluster status and modulates the expression of the sole Fe-S cluster assembly system via its Fe-S cluster occupancy. IMPORTANCE Fe–S clusters function as cofactors of proteins controlling diverse biological processes, such as respiration, photosynthesis, nitrogen fixation, DNA replication, and gene regulation. The mechanism of how Actinobacteria regulate the expression of the sole Fe-S cluster assembly system in response to the various Fe–S cluster demands remains to be elucidated. In this study, we showed that SufR functions as a transcriptional repressor of the sole Fe-S cluster assembly system in the avermectin producer S. avermitilis. [4Fe-4S]-SufR binds to the promoter region of the suf operon and represses its expression. When Fe-S cluster levels are insufficient, SufR loses its [4Fe-4S] cluster and DNA-binding activity. Apo-SufR dissociates from the promoter region of suf operon, and the expression of the suf system is strongly increased by derepression to promote the synthesis of Fe-S clusters. The study clarifies how Streptomyces maintains its Fe-S cluster homeostasis through the activity of SufR to modulate the various Fe-S cluster demands.